2007
DOI: 10.1152/jn.00443.2006
|View full text |Cite
|
Sign up to set email alerts
|

Internal Pallidal Neuronal Activity During Mild Drug-Related Dyskinesias in Parkinson's Disease: Decreased Firing Rates and Altered Firing Patterns

Abstract: The neuronal basis of hyperkinetic movement disorders has long been unclear. We now test the hypothesis that changes in the firing pattern of neurons in the globus pallidus internus (GPi) are related to dyskinesias induced by low doses of apomorphine in patients with advanced Parkinson's disease (PD). During pallidotomy for advanced PD, the activity of single neurons was studied both before and after administration of apomorphine at doses just adequate to induce dyskinesias (21 neurons, 17 patients). After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 59 publications
9
34
0
Order By: Relevance
“…Alonso-Frech et al (2006) found basically the same results and suggested that the increase in the power of the 4-10 Hz frequency band could account for dopamineinduced dyskinesias in PD patients. This has been also pointed out more recently by Lee et al (2007) who observed that a decrease in neuronal firing rate in the GPi preceded the onset of dyskinesias induced by the administration of apomorphine. Kuhn et al (2006b) calculated in 9 PD patients the STN LFP power over the frequencies of the most prominent spectral peak within the 8-35 Hz frequency band and of any peak in the 60-90 Hz band.…”
Section: Effects Of Disease and Treatment On Neuronal Activity In Thesupporting
confidence: 57%
“…Alonso-Frech et al (2006) found basically the same results and suggested that the increase in the power of the 4-10 Hz frequency band could account for dopamineinduced dyskinesias in PD patients. This has been also pointed out more recently by Lee et al (2007) who observed that a decrease in neuronal firing rate in the GPi preceded the onset of dyskinesias induced by the administration of apomorphine. Kuhn et al (2006b) calculated in 9 PD patients the STN LFP power over the frequencies of the most prominent spectral peak within the 8-35 Hz frequency band and of any peak in the 60-90 Hz band.…”
Section: Effects Of Disease and Treatment On Neuronal Activity In Thesupporting
confidence: 57%
“…This implied that the irregular firing pattern might be stochastic. The irregular firing patterns of neurons in the globus pallidus internus (GPi) were related to dyskinesias induced by low doses of apomorphine in patients with advanced PD [64]. After the apomorphine injection, the behavior of patients often fluctuated between transient periods being dyskinesias and those without dyskinesias.…”
Section: Experimental Results Of Nonlinear Dynamic Behavior Of Stochamentioning
confidence: 99%
“…Dyskinesias have been associated with reduced pallidal firing rates and altered firing patterns [26,27] as well as increased pallidal neuronal synchronisation at low frequencies (<10 Hz) [28,29,30,31]. The use of GPi stimulation for the treatment of dyskinesias is well supported by the literature [32,33,34,35], and it is likely that the success of this procedure is in part related to inhibition of aberrant neuronal activity at this nucleus [36,37,38].…”
Section: Discussionmentioning
confidence: 99%